Cartografias urbanas : o processo de (des)reterritorialização politica da revisão do plano diretor de Maringá (2019/20) - Pires, Lucio Paulo Alves (2021)
I invite all (a, an) to the deterritorializing movement, to the affirmation of a devir-research, through the threads that ask for passage, which are inscribed in the production of territorial urban policy, in art of cartographic micropolitical composition. With this work, we claim to have the will to power from its clues that follow ontologically in becoming, a schizoanalysis proposed by Gilles Deleuze and Felix Guattari (1968). We looked at the multipli-cities and built cartographies as we followed the process of reviewing the Master Plan in the municipality of Maringá, in the years 2019/20. We cartography the macro and micropolitical crossings in this process, everything that affected us and is defined in desire, in event. This coextensive and immanent connection between the molar (macropolitical) and molecular (micropolitical) planes potentiated our affections: of the bodies; of the common plans; of the encounters; public policies; of social movements; enunciating singularities, giving way and establishing the cartographic process. In this movement, we produce the diversity of urban plateaus (cartographies), in singularization and production of subjectivities, experiencing processes of (de)reterritorialization and transvaluation of the self, from delusional movements, of escape and resumption. It is composed of an artistic feeling, the creation of worlds through the plan of becoming. As a result, in constant movement, our drifts are (in)conclusive, but we affirm, in the diversity of fields constructed in organizational studies and in public administration, a declaration of war: a policy-without-organs.